การแสดงบทบาทคาดหวังของผู้บริหารสตรีในองค์การ : ศึกษากรณีบริษัท ทศท. คอร์ปอเรชั่น จำกัด (มหาชน) - ชนาภา สุริโย (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This study intends to investigate how the TOT Corporation Public Company Limitedʼs executive women perceive and enact their social and organizational roles and to identify factors that effect their role and role conflict. The naturalistic inquiry is used in accordance with documentary and field research. The non-participative observation is used to collect data by using in-depth interviews with the 10 executive women. The research reveals that the executive women recognize their social and organizational expected roles at a high level and are able to enact their social roles at a high level as well, but they enact their organizational roles at a medium level. Regarding to role conflicts, it is found that these executive women tend to have highest conflicts in their motherʼs roles, followed by conflict in their administrative roles, daughterʼs roles and wifeʼs roles consecutively. Factors which affect the executive womenʼs role enactment are their high expectation in performing the roles; economic difficulties and their needs for more private time. In order to solve conflicts in their social expected role enactment, these executive women try to find some assistants to help them perform the roles. As for the organizational expected roles, the executive women solve their role conflicts by participating in the organizationʼs early retire program.